Theatre and culture in early modern England, 1650-1737 : from Leviathan to Licensing Act - Gill, Catie (Ashgate, 2010)
Framed by the publication of Leviathan and the 1713 Licensing Act, this collection provides analysis of both canonical and non-canonical texts within the scope of an eighty-year period of theatre history, allowing for definition and assessment that uncouples Restoration drama from eighteenth-century drama. Paying special attention to literary innovation and sociopolitical changes, this book is a valuable tool for scholars of Restoration and eighteenth-century performance, providing groundwork for future research and investigation.